Novel Microsatellite Markers for Osmia lignaria (Hymenoptera: Megachilidae): A North American Pollinator of Agricultural Crops and Wildland Plants. Issue 1 (5th January 2023) - Koch, Jonathan Berenguer Uhuad; Branstetter, Michael G; Cox-Foster, Diana L; Knoblett, Joyce; Lindsay, Thuy-Tien Thai; Pitts-Singer, Theresa L; Rohde, Ashley T; Strange, James P; Tobin, Kerrigan B
Abstract: Comprehensive decisions on the management of commercially produced bees, depend largely on associated knowledge of genetic diversity. In this study, we present novel microsatellite markers to support the breeding, management, and conservation of the blue orchard bee, Osmia lignaria Say (Hymenoptera: Megachilidae). Native to North America, O. lignaria has been trapped from wildlands and propagated on-crop and used to pollinate certain fruit, nut, and berry crops. Harnessing the O. lignaria genome assembly, we identified 59, 632 candidate microsatellite loci in silico, of which 22 were tested using molecular techniques. Of the 22 loci, 12 loci were in Hardy-Weinberg equilibrium (HWE), demonstrated no linkage disequilibrium (LD), and achieved low genotyping error in two Intermountain North American wild populations in Idaho and Utah, USA. We found no difference in population genetic diversity between the two populations, but there was evidence for low but significant population differentiation. Also, to determine if these markers amplify in other Osmia, we assessed 23 species across the clades apicata, bicornis, emarginata, and ribifloris . Nine loci amplified in three species/subspecies of apicata, 22 loci amplified in 11 species/subspecies of bicornis, 11 loci amplified in seven species/subspecies of emarginata, and 22 loci amplified in two species/subspecies of ribifloris . Further testing is necessary to determine the capacity of these microsatellite loci to characterize genetic diversity and structure under the assumption of HWE and LD for species beyond O. lignaria . These markers will inform the conservation and commercial use of trapped and managed O. lignaria and other Osmia species for both agricultural and nonagricultural systems.